2009
DOI: 10.1177/0022034509347090
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T-cells in Periapical Lesions

Abstract: CD4(+)CD25(hi)Foxp3(+) regulatory T-cells (Tregs) are of crucial importance in regulating the immune response, including the control of any defense against infection. Their presence in periapical lesions has not been demonstrated, as yet. We hypothesized that Tregs infiltrate periapical lesions, where they inhibit T-cell proliferation. The aim of this study was to characterize Tregs in periapical lesions by confocal microscopy, flow cytometry, and functional assays. We showed that CD4(+)CD25(hi)Foxp3(+) cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 34 publications
4
51
0
2
Order By: Relevance
“…In phase 2, the full-text of 18 studies were retrieved and evaluated. Of those, only eight 14,15,16,17,18,19,20,21 met the eligibility criteria. No additional study was identified in the reference lists of the included articles and in the grey literature.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…In phase 2, the full-text of 18 studies were retrieved and evaluated. Of those, only eight 14,15,16,17,18,19,20,21 met the eligibility criteria. No additional study was identified in the reference lists of the included articles and in the grey literature.…”
Section: Study Selectionmentioning
confidence: 99%
“…14,15,18,21 All studies involved human periapical lesion fragments. Samples of six articles 14,15,18,19,20,21 were obtained directly through surgery and samples of the other two studies were obtained through institutional archives collected from previous surgical procedures. 16,17 Fou r a r t icles repor ted t he mea n age of participants 18,19,20,21 and five studies defined the range between 17 and 64 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations